Strategic, Geographic Targeting of Housing and Community Development Resources: A Conceptual Framework and Critical Review. - Thomson, Dale E. (Urban Affairs Review, 2008)
This article critically examines a conceptual framework for strategic, geographic targeting, an allocation model for improving efficiency in community development programs. It reviews the theoretical and empirical literature, discusses constraints and policy implications, and outlines a research agenda. Cost-savings, multiplier, and interaction effects form the core rationale for strategic, geographic targeting. Focus and neighborhood spillover effects complement these and are likely to occur more rapidly when strategic, geographic targeting is used. While the literature is largely silent on the cost-savings, focus, and neighborhood spillover effects, it supports the multiplier effect and demonstrates that it is contingent on the attainment of investment thresholds. It also identifies interventions that are likely to interact positively with programs targeting housing investment. Reprinted by permission of the publisher.